(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Banks are back bone to the financial economy of every country. In consonance, huge amount of loans has turned in to toxic assets. Higher NPA impact the revenue strength of the banks and also lose the confidence level of consumers and depositors, banks are back bone to the financial economy of every country. The Gross NPA exists into sector is highest for Industry and Agriculture followed by Services and Personal loans. The problem of non-performing loans continues to expand, while lending and investment continue to decline, having a negative effect on the whole economy. The corona virus epidemic has wreaked havoc on banks and financial institutions worldwide, since the global economic crisis has resulted in an increase in defaults and bad loans. At a time when the country is on the threshold to achieve the desired growth, non performing asset has also become hindrance. In order to clean up the balance sheet of the banks, the state says that Bad Bank will provide financial stability in the banking sector. This paper will make an attempt to examine the pros and cons of the bad bank.